Insight of Tp53 Mutations and their effect on Protein in Different Feline and Canine Neoplasms - Rashid Saif (Advancements in Life Sciences, 2016)
Background: Mutations in the Tp53 gene, a tumor suppressor gene, may cause dysfunction in growing cells and hinder the phenomenon of apoptosis, an alleged cause of tumorigenesis. It is involved in conservation of the genome and DNA repair, mutations of this gene may cause the damaged cells to grow continuously. Methods: The type of molecular changes in Tp53 gene and their effects on physiochemical and structural properties of this protein in various Canine and Feline cancers were observed in this study by using online bioinformatics tools. Results: Our results indicated that lymphomas and perianal adenocarcinomas (PAC) have the same mutation at c. 104, while mammary tumors and canine transmissible venereal tumor (CTVT) contain different mutations. Referring to changes in protein, synonymous mutations in granulomas were observed while certain mutations in squamous cell carcinoma (SCC) and head & neck tumors were detected in Canis familiaris. In Felis catus, the mutant protein was similar to wild type protein with exception of mutant 5 of mammary tumor, which had a deletion at the 287 amino acid position. Conclusion: The insight gathered on the p53 mutant proteins in both species aided our understanding of the in-vivo fate of the p53 protein and its isoforms and the effects that morphological changes can have on the fate of cells. Furthermore, isolation of this protein may augment our understanding about the structural biology of these proteins.